PENGARUH KETERBUKAAN DIRI TERHADAP KETRAMPILAN KOMUNIKASI INTERPERSONAL PADA PENGURUS MAHASISWA PECINTA ALAM INSTITUT ISLAM MAMBA’UL ‘ULUM SURAKARTA TAHUN 2022 - Faurina Nurhanifa; Arif Effendi (Jurnal Inovasi Penelitian, 2022)
Faurina Nurhanifa and Arif Effendi, thesis, The effect of self disclosure on interpersonal communication skills for the nature-loving student management of Surakarta Mamba’ul ‘Ulum Islamic Institute in 2022, Surakarta Mamba’ul ‘Ulum of Islamic Instutute. This research wish to know the self disclosure of the student management for nature lovers of Surakarta Mamba’ul ‘Ulum Islamic Institute ; wish to know the interpersonal communication skills of the student management for nature lovers of Surakarta Mamba’ul ‘Ulum Islamic Institute ; and wish to know the correlation between self-disclosure and interpersonal communication skills on the management for nature lovers of Surakarta Mamba’ul ‘Ulum Islamic Institute. This research is a type of correlational quantitative research that correlates two variables, Subject in this study are the student management for nature lovers of Surakarta Mamba’ul ‘Ulum Islamic Institute with a population of 32 peopples with no sample. The data analysis technique to test the hypothesis in this study is to use the Product Moment correlation analysis technique. The results showed that the self-disclosure of the student management for nature lovers of Surakarta Mamba’ul ‘Ulum Islamic Institute was in the enough category ; the interpersonal communication skills of the student management for nature lovers of Surakarta Mamba’ul ‘Ulum Islamic Institute was in the enough category ; The results of correlation are r xy = 0,73 or the category is acceptable